Quark structure of the nucleon and moat regimes in nuclear matter - Motta, Theo F. [UNESP]; Krein, Gastão [UNESP] (American Physical Society (APS), 2025)
We employ a model of nuclear structure that takes into account the quark substructure of the baryons to understand the behavior of static two-point correlation functions of meson fields in dense nuclear matter. We show that these correlation functions display “moat” regimes, where the inverse static correlation function is nonmonotonic in momentum space. This can have interesting consequences for the nature of nuclear matter, and it strengthens the possibility of a liquid-crystal phase for high densities.